P180 Impact of the london low emission zone on children's respiratory health: a sequential yearly cross sectional study 2008–2014. (15th November 2016) - Griffiths, CJ; Mudway, I; Wood, H; Marlin, N; Dundas, I; Walton, R; Grigg, J; Sheikh, A; Lee, T; Kelly, F
Abstract : Background: Low Emission Zones are a novel public health intervention to address the adverse effects of traffic pollution on health. We investigated the association between traffic derived air pollutants and lung function in 8–9 year old children living in London's Low Emission Zone. Methods: Sequential yearly cross-sectional study of 2, 297 children aged 8–9 years attending east London primary schools between 2009 and 2014, following the introduction of the Low Emission Zone. We examined the relationship between pollutant exposures (NOx, NO2, PM2.5 and PM10) and lung function. We assigned annual exposures by each child's residential address. In addition, we used spatially resolved estimates of 12-hour, 24-hour, 7-day and annual exposures prior to each child's assessment, allowing us to compare the relative effects of very short-, short-, medium- and long-term pollutant exposures. Primary outcome measure was post-bronchodilator FEV1. Findings: We found inverse associations between exposures of PM10 and PM2.5 in the week prior to children's assessment and FEV1 (P < 0.05); and inverse associations between annual exposures of PM10, NOx, and NO2, and FVC (p < 0.05); and exposures of PM10 and PM2.5 in the week prior to assessment, and FVC (p < 0.05). No associations were seen when shorter term exposure estimates were employed. We found no evidence of improvements in lung function over the duration of the Low Emission Zone. Interpretation: Exposure of children to traffic pollution in central London is associated with decreased lung function and lung volumes. No detectable health benefit followed the introduction of the Low Emission Zone.